2018
DOI: 10.1101/gr.241257.118
|View full text |Cite
|
Sign up to set email alerts
|

Long-read sequencing technology indicates genome-wide effects of non-B DNA on polymerization speed and error rate

Abstract: Service Email Alerting click here. top right corner of the article or Receive free email alerts when new articles cite this article-sign up in the box at the http://genome.cshlp.org/subscriptions

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 72 publications
(95 reference statements)
9
62
0
Order By: Relevance
“…While Illumina reads always represent short fragmented DNA, long DNA molecules used for PacBio and Nanopore sequencing could form secondary structures. We have recently shown that non-B DNA structures can affect PacBio sequencing depth and error rates (Guiblet et al 2018) . For Nanopore, fragments harboring these structures might not pass through the pores.…”
Section: Interspecific Differences and Lack Of Phylogenetic Signal Inmentioning
confidence: 99%
“…While Illumina reads always represent short fragmented DNA, long DNA molecules used for PacBio and Nanopore sequencing could form secondary structures. We have recently shown that non-B DNA structures can affect PacBio sequencing depth and error rates (Guiblet et al 2018) . For Nanopore, fragments harboring these structures might not pass through the pores.…”
Section: Interspecific Differences and Lack Of Phylogenetic Signal Inmentioning
confidence: 99%
“…However, it remains unclear if this applies to sequence fragments with > 60% GC content; specifically whether read depth sequence errors are within acceptable limits using PacBio technology. Furthermore, at the same time as this manuscript was reviewed another study was published [33] which evaluated the efficiency of PacBio reads for sequencing non-B DNA regions in human and mouse genomes. This study showed that non-B DNA regions modified the polymerization speed and the error rate, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…regions able to determine non-B structures plus their single-stranded DNA environment due to transitions between B and non-B DNA) represent about 13% of the studied genomes [34, 35]. Among the seven kinds of non-B DNA determinants that were investigated, they showed [33] that mammalian regions containing stretches of direct repeats and were composed mostly of G-quadruplexes (G4; i.e. regions containing the motif G 3 + N1-12 G 3 + N 1-12 G 3 + N 1-12 G 3 where N is any base including G) had pronounced effects on read depth and the error rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several important discoveries have already been made from this kinetic information, such as the widespread presence of 6mA modifications in the human genome [6], a modification that was previously thought to only be present in bacterial genomes. In addition to base modifications, SMRT sequencing data also enables us to study other events, such as DNA conformations [7]. Another aspect of SMRT sequencing is that it can be used to study RNA, and it is currently the only technology that can generate high-quality continuous sequences for full-length transcripts up to 10 kb or more.…”
mentioning
confidence: 99%